In Vitro Modulation Of Cytochrome P450 Isozymes And Pharmacokinetics Of Caffeine By Extracts Of Hibiscus Sabdariffa Linn Calyx (2019)
Background: Hibiscus sabdariffa beverage (HSB) is widely consumed as a medicinal herb and sometimes used concomitantly with drugs. This study evaluated the in vitro inhibitory potential of the aqueous extract of H. sabdariffa calyces (AEHS) on selected cytochrome P450 (CYP) isozymes and the effect of HSB on the pharmacokineticsofcaffeineinvivo. Methods:InvitroinhibitionsofeightmajorCYPisozymesbyAEHSwereestimatedbymonitoringCYP-specific modelreactionsof10CYPprobesubstratesusingN-in-oneassaymethod.Subsequently,anopen,randomized, two-periodcrossoverdesignwasusedtoevaluatetheeffectofHSBonthepharmacokineticsofsingle-dose200 mg caffeine in six healthy human volunteers. Blood samples were obtained at specific times over a 24 h period. Probe drugs and metabolites were analyzed in their respective matrices with ultra-performance liquid chromatography/mass spectrometer/mass spectrometer and reversed-phase high-performance liquid chromatography/ultravioletdetection. Results:TheH.sabdariffaaqueousextractweaklyinhibitedtheselectedCYPisozymesinvitro,withIC50of >100 μgmL-1 intheorderofCYP1A2>CYP2C8>CYP2B6»CYP2D6>CYP2C19>CYP3A4>CYP2A6>CYP2C9. HSBdecreasedterminalt1/2andTmaxofcaffeineby13.6%and13.0%,respectively,andincreasedCmaxby10.3%. Pointestimatesofprimarypharmacokineticendpoints,Cmax=1.142(90%confidenceinterval(CI)=0.882,1.480) andAUC0–∞=0.992(90%CI=0.745,1.320),wereoutsidethe90%CIof0.8–1.25bioequivalencelimits. Conclusion:TheaqueousextractofH.sabdariffaweaklyinhibitedeightCYPisozymesinvitro,butHSBmodified theexposuretocaffeineinhuman.CautionshouldbeexercisedinadministeringHSBwithcaffeineorsimilar substratesofCYP1A2untilmoreclinicaldataareavailable.